Solitary Celiac Lymph Node Metastasis Has a Better Long-Term Survival Compared With Solitary Mediastinal Lymph Node Metastasis in Esophagectomy of Esophageal Squamous Cell Cancer: A Propensity Score Matching Analysis - Li, Kun-Kun; Bao, Tao; Wang, Ying-Jian; Zhao, Xiao-Long; Long, Jiang; Xie, Xian-Feng; Guo, Wei (Frontiers in Oncology, 2022)
Background The prognostic benefit of extensive lymphadenectomy remains controversial in esophageal squamous cell carcinoma (ESCC). The purpose of this retrospective study was to investigate the potential effect of solitary mediastinal (SM) lymph node metastasis and solitary celiac (SC) lymph node metastasis on the short- and long-term outcomes for patients who underwent minimally invasive McKeown esophagectomy. Methods From September 2009 to December 2020, a total of 934 cases were diagnosed with ESCC and underwent minimally invasive Mckeown esophagectomy in our department, 223 cases met the inclusion and exclusion criteria. Propensity score matching (PSM) was utilized to contrast the postoperative results and long-term survival of Group 1 (SM) and Group 2(SC). Univariate and multivariate Cox proportional hazard regression analysis was used on possible predictors of survival. Results One hundred and forty-seven patients were available for outcome comparison after PSM, the postoperative results weren’t significantly different between the two groups. In terms of long-term survival, the five-year DFS was 37.6%and 57.3% (p = 0.191) and five-year DSS was 39.7% and 68.4% (p = 0.028) for Group 1(SM) and 2 (SC), respectively. Univariate and multivariate Cox proportional hazard regression analyses showed that BMI, pStage, and SC/SM Grouping had significant HRs, which suggested that SC is associated with better DSS. Conclusion This cohort study showed that SC lymph node metastasis has a better long-term survival compared with SM lymph node metastasis in esophagectomy of ESCC, the results challenge the current understanding and need confirmation in further research.